Electrochemical studies on Langmuir-Blodgett films of 1-tert-butyl-1,9- dihydrofullerene-60 - Goldenberg, Leonid; Williams, Geoffrey; Bryce, Martin R.; Monkman, Andrew P.; Petty, Michael C.; Hirsch, Andreas; Soi, Antonio (Journal of the Chemical Society - Series Chemical Communications, 1993)
Langmuir-Blodgett (LB) films of 1-tert-butyl-1,9-dihydrofullerene-60 are shown to undergo well defined multistage electrochemical reductions to yield the trianion species, with the first two redox waves stable to recycling; these data contrast with those for LB films of the parent system C .